Effects Of A New Drinkers Prevention Program For Primary School Students, Surin Province - สาลีงาม, วิจิตรา; รวิวรกุล, ทัศนีย์; จิระพงษ์สุวรรณ, แอนน์; สมภพเจริญ, มลินี (Journal of The Royal Thai Army Nurses, 2019)
This quasi-experimental study aimed to examine effects of a new drinker prevention program for primary school students, Surin province, Thailand. Samples were grade 5 -6 students from two primary schools in Sangkha district, divided into the experimental group (14 students) and the comparison group (15 students). Theory of planned behavior was derived into the a 3-week new drinker prevention program to enhance perceived attitude toward alcohol drinking behavior, perceived subjective norm to not alcohol drinking behavior, perceived behavioral control for not drinking alcohol beverage, and intention to not drink alcohol. Data collection was done at pre-test and at the 4th week after completion of the program. Descriptive statistics, independent t-test and paired t-test were performed for data analysis. Results reveal that, at post-test, only perceived behavioral control for not drinking alcohol beverage and intention to not drink alcohol in the experimental group show a greater mean score than the pre-test mean score (p-value = .009 and 0.028 ). At post-test, only the attitude toward alcohol drinking behavior mean score in the experimental group was found greater than the comparison group (p-value = .017).